Third Language Acquisition: A Systematic Review - Icha Fadhilasari (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The phenomenon of third language acquisition has spread rapidly in recent decades, as one of the multifaceted effects of the current era of globalization. In a world where multilinguals outnumber monolinguals, the study of third language (L3) acquisition has become an area of ​​interest for many researchers. This article aims to provide an overview of reviews of several studies regarding third language acquisition.A systematic review method was used in this study, based on research questions that govern which studies will be included for review. This study aims to investigate research trends on third language acquisition. The results of this research show that several studies after 2020 only focused on transfer errors due to cross-linguistic influences at the morphosyntactic level.